The Implementation of The Complete Systematic Land Registration Program as A Framework for Achieving Agrarian Reform - Ardhana, Azriel Putra; Taupiqqurrahman (JURNAL MERCATORIA, 2024)
This research aims to analyze the implementation of the Complete Systematic Land Registration (PTSL) program as an effort to accelerate Agrarian Reform, which aims to create justice and welfare for the people as mandated by the Constitution. The issue is focused on the agenda of accelerating Agrarian Reform through the Complete Systematic Land Registration, which has proven to have a positive impact on Indonesian society in terms of providing legal certainty of land ownership, thereby preventing the potential for agrarian conflicts. This research uses qualitative methods with a legislative approach and a conceptual approach, resulting in a juridical-normative type of study. Data were collected through unstructured observation methods and analyzed qualitatively. This study concludes that land registration in Indonesia until 2017 (before the PTSL program) only resulted in 46 million registered land parcels, whereas as of now, it has reached 117.9 million registered land parcels by September 2024. With the existence of land ownership certificates as proof of ownership, it will be able to provide legal certainty and minimize agrarian conflicts, thereby enabling the government's efforts in the Acceleration of Agrarian Reform to be achieved effectively.